Los Angeles Dodgers 5 vs Atlanta Braves 2 at Dodger Stadium - Watkins, Howard::::::::: (1987)
Dodger fans give standing ovation to pitcher Sean Hillegas #57 for his winning pitching debut Viewed from centerfield